Can 2,4-D promote the hormesis effect in upland rice? - Marsala, Leonardo [UNESP]; Oliveira Cunha, Matheus Luís [UNESP]; do Nascimento, Vagner [UNESP]; Pereira Prado, Evandro [UNESP]; da Silva Viana, Ronaldo [UNESP]; Ferrari, Samuel [UNESP] (Taylor & Francis, 2022)
This study aimed to evaluate the influence of low doses of 2,4-D on the agronomic traits of upland rice applied at different stages of crop growth. The work was carried out in a randomized completly blocks, and consisted of the application of 5 low doses of the 2,4-D herbicide (0, 0.68, 1.36, 2.04, 3.40 and 5.44 g acid equivalent (e.a.) ha−1) in two stages of rice development (tillering and floral differentiation). Nitrogen contentes in leaves, SPAD index and yield are higher when low doses of 2,4-D is applied in the tillering stage. Application of 2,4-D at a dose of 2.04 g a.e ha−1 results in a 19% increase in the number of spikelet per panicle. On the other hand, there is no effect of the application of low doses of 2,4-D on height, number of stems, active tillering and weight of 100 seeds. Our results contribute to increase knowledge of the hormesis effect in plants in order to increase crop yield.
Keywords: Height; herbicide; hormesis effect; spikelet per panicle; yield